Eight Kinds of Critters: A Moral Taxonomy for the Twenty-Second Century. - Bess, Michael (Journal of Medicine & Philosophy, 2018)
Over the coming century, the accelerating advance of bioenhancement technologies, robotics, and artificial intelligence (AI) may significantly broaden the qualitative range of sentient and intelligent beings. This article proposes a taxonomy of such beings, ranging from modified animals to bioenhanced humans to advanced forms of robots and AI. It divides these diverse beings into three moral and legal categories-animals, persons, and presumed persons-describing the moral attributes and legal rights of each category. In so doing, the article sets forth a framework for extending the concept of personhood well beyond its current boundaries, assigning moral standing to a variety of biological and nonbiological beings. The author concludes that six of the eight subgroups of such beings deserve to be treated as persons or as if they were persons, with full consideration for their presumed interests, rights, obligations, and capabilities for ethically significant agency and patiency.